Evaluation of the myogenic effects of subthalamic nucleus deep brain stimulation at near therapeutic amplitudes - Toth, Carmen; Campbell, Brett A.; Bocca, Leonardo Favi; Baker, Kyle; Hogue, Olivia; Tiefenbach, Jakov; Negrey, Jeffrey; Cunningham, David; Machado, André G.; Baker, Kenneth B. (Frontiers in Neuroscience, 2026)
IntroductionSubthalamic nucleus deep brain stimulation (STN-DBS) is a standard-of-care (SoC) treatment for the motor symptoms of Parkinson’s disease (PD); however, how therapeutic DBS influences motor output is incompletely understood. Specifically, the extent of electromyographic (EMG) modulation during DBS at therapeutic (or SoC) amplitude and its relationship to activity state could be better characterized.MethodsWe studied the effects of DBS on muscle activity in sixteen participants receiving STN-DBS (in 17 stimulated hemispheres) by recording EMG activity in bilateral biceps, triceps, flexor carpi radialis, and extensor digitorum communis muscles. Data was acquired in the resting state and while participants alternated between isometric contraction and brief relaxation. We recorded EMG activity during low-frequency stimulation at participant-specific therapeutic amplitude and during stimulation using pulse amplitudes slightly above (125%) and below (75%) this level. Stimulus-locked responses from each condition were evaluated for the presence of a myogenic evoked potential.ResultsDBS at therapeutic amplitude elicited a myogenic response almost exclusively in the contralateral upper extremity (CUE), with at least one response occurring in 16 out of 17 hemispheres. Myogenic responses, which typically started between 10-30 milliseconds and often lasted until ~70-150 milliseconds post-stimulation, were more common in biceps/triceps. Responses were more prevalent during active contraction compared to relax/rest states as stimulation amplitude increased.DiscussionThese findings support that STN-DBS-induced myogenic activity is commonplace at therapeutic stimulation amplitudes used clinically; thus, studies evaluating the degree to which myogenic effects during SoC STN DBS are associated with the clinical and side effects of STN DBS therapy are warranted.